Anti-inflammatory and antioxidant effects of Pogostemon stellatus (Lour.) Kuntze via MAPK, NF-κB, and Nrf2 signaling pathways in LPS-activated RAW 264.7 macrophages - Yoon, Haelim; Gong, You Li; Seo, Jihye; Kim, Jiyu; Uddin, Md. Salah; Han, Sang Beom; Cho, Sayeon (Frontiers in Pharmacology, 2025)
BackgroundPogostemon stellatus (Lour.) Kuntze is a plant native to South and East Asia belonging to the Lamiaceae family, whose members are widely recognized for their anti-inflammatory and antioxidant properties. However, these properties have not been extensively studied in P. stellatus (Lour.) Kuntze. This study aimed to evaluate the anti-inflammatory and antioxidant effects of methanol extract of P. stellatus (Lour.) Kuntze (MPSK) in LPS-stimulated RAW 264.7 macrophages.MethodsRAW 264.7 macrophages were stimulated with LPS and treated with MPSK. Anti-inflammatory effects were assessed by measuring nitric oxide (NO) and prostaglandin E2 (PGE2) levels and the expression of inducible NO synthase (iNOS), cyclooxygenase-2 (COX-2), interleukin-6 (IL-6), interleukin-1β (IL-1β), and tumor necrosis factor-α (TNF-α) at both mRNA and protein levels. Nuclear factor-κB (NF-κB) and mitogen-activated protein kinase (MAPK) pathway involvement was examined. Antioxidant capacity was determined using a DPPH radical scavenging assay, and nuclear factor erythroid 2-related factor 2 (Nrf2) and its downstream targets were evaluated.ResultsMPSK markedly attenuated the production of inflammatory mediators and cytokines in LPS-induced RAW 264.7 macrophages. NO production was suppressed by 98%, compared with the LPS-treated group. PGE2 production was also inhibited by 64%. Consistent with these findings, MPSK significantly reduced the protein and mRNA expression levels of iNOS and COX-2. Furthermore, MPSK suppressed the production and expression of pro-inflammatory cytokines, including IL-1β, IL-6, and TNF-α. Notably, when MPSK was administered at 100 μg/mL, IL-6 and IL-1β production were reduced by 21% and 18%, respectively, compared with the LPS-treated group. These anti-inflammatory effects were associated with the inhibition of NF-κB and MAPK signaling pathways. Immunoblot analysis demonstrated that NF-κB protein expression was reduced by 72% upon treatment with MPSK, while the phosphorylation of ERK, JNK, and p38 was suppressed by 38%, 56%, and 35%, respectively. MPSK suppressed ROS levels in RAW 264.7 cells by 62%, demonstrating its potent antioxidant capacity. This antioxidant activity of MPSK was demonstrated by the upregulation of Nrf2 and its downstream antioxidant target genes.ConclusionMPSK possesses both anti-inflammatory and antioxidant activities through regulation of NF-κB, MAPK, and Nrf2 pathways, suggesting its potential as a therapeutic agent against inflammation and oxidative stress.